Andrographis Paniculata As Potential Sensitizing Agent Towards Antibiotic - Chung, Chee Hooi (2018)
Antibiotic resistance is the ability of microbes to resist antibiotic action despite of increasing concentration, and plan extracts have shown potential as the antibiotic sensitizing agent to reduce the dosage of antibiotic use. So, in this study, ethanolic extract of Andrographis Paniculata was screened for antimicrobial property using modified Kirby Baucer disc diffusion assay. The results showed significant growth inhibition (p<0.05) of Pseudomonas aeruginosa, exhibited through the formation of zone of inhibition. The subsequent minimum inhibitory concentration (MIC) for the ethanolic extract .of A. paniculata was determined to be 25 mg/mL, which was the minimum concentration that significantly inhibited (p<0.05) the growth of P. aeruginisa. This MIC of A. paniculata was used to proceed with anti-adhesion assay and the results reported no significant (p>0.05) inhibition on bacterial cells adhesion, thus suggesting no inhibition on the biofilm formation of P. aeruginosa. Although A. paniculata ethanolic extract did not exhibit anti biofilm formation as the mode of action to inhibit growth of P. aeruginosa, the overall results suggest that A. paniculata can be still a godd candidate as a sensitizing agent towards antibiotics due to the strong antimicrobial activity demonstrated.